Exploring Indonesian EFL learners’ extramural English activities - Emeral, Emeral; Yulitriana, Yulitriana (TLEMC (Teaching and Learning English in Multicultural Contexts), 2025)
Extramural English, also known as English exposure beyond the classroom, has become increasingly relevant for language learning, especially with technological advancements. To better understand how extramural English contributes to the English learning process in the Indonesian context, this study explores the extramural English activities of Indonesian EFL learners. A total of seventy-three university students majoring in English Language Education participated in a survey, which gathered data on their extramural English preferences and perceived benefits for language skills. The data were then thematically analyzed. The findings revealed that receptive-related activities were the most popular, with participants frequently engaging in listening to English songs (94.5%), watching music videos with English captions (82.2%), and watching films or TV series in English with Indonesian subtitles (76.7%). These activities were favored because they were enjoyable and provided opportunities for English development. Moreover, most participants perceived extramural English as beneficial for enhancing their knowledge of language items, language skills, and cultural understanding. The findings suggest that EFL teachers should incorporate more productive extramural English tasks to promote balanced skill development among learners.  Keywords: Extramural English, digital learning, English development